Prediction of deflection from flatness and a vertical position with the use of neural networks = Predykcja odchyleń od płaskości i pozycji pionowej z zastosowaniem sieci neuronowych - Mrówczyńska, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents an attempt to apply unidirectional multilayer neural networks in the prediction of the deflections from flatness and from a vertical position of building walls, on an example of periodic measurements in the church of the Blessed Virgin Mary in Toruń.
Keywords: sieci neuronowe; odchylenia od płaskości; predykcja odchyleń; kościół Najświętszej Maryi Panny (Toruń); neural networks; deflections from flatness; prediction; church of the Blest Virgin Mary (Toruń)